Discrepancies in the Diagnosis of Congenital Toxoplasma gondii Infection Between B1 Gene Semi-Nested Polymerase Chain Reaction and Serological Analyses - Akiko Uchida; Kenji Tanimura; Keisuke Shirai; Mariko Ashina; Kazumichi Fujioka; Ichiro Morioka; Miwa Sasai; Masahiro Yamamoto; Hideto Yamada (Microorganisms)
Congenital Toxoplasma gondii (T. gondii) infection, which can be caused by a primary T. gondii infection during pregnancy, results in severe neurological sequelae in affected children. We have been conducting a prospective cohort study since January 2019 on pregnant women who were suspected of having primary T. gondii infection based on serological tests. In this study, congenital infection was diagnosed using semi-nested polymerase chain reaction (PCR) to detect the B1 gene in the body fluids of newborns. Up until December 2023, forty-one newborns born to mothers suspected of having primary T. gondii infection during pregnancy underwent B1 gene semi-nested PCR tests and anti-T. gondii immunoglobulin (Ig) G and IgM measurements of their blood samples. Eight newborns showed no clinical symptoms of congenital T. gondii infection; however, they were diagnosed with congenital T. gondii infection according to positive PCR results. However, none of the eight infants eventually exhibited any sign of congenital infection, as their serum samples tested negative for anti-T. gondii IgM and IgG until 12 months of age. Therefore, clinicians should consider discrepancies in the diagnosis of congenital T. gondii infection between PCR tests using body fluids of newborns and serological tests during their infantile period.